Resource-Efficient and Resilient SOC/SOH Co-Monitoring of EV Batteries With Attack Detection - Xiao, Shunyuan; Ding, Lei; Ye, Maojiao; Yue, Dong; Ge, Hui (IEEE transactions on smart grid, 2025)
A co-monitoring problem of state of charge (SOC) and state of health (SOH) under resource-constrained and insecure communication is addressed in this paper. First, an SOC/SOH co-monitoring framework is established to account for battery SOC and SOH dynamics, unknown-but-bounded (UBB) process and measurement noises, dual coupled monitors, and intermittent measurement updates at multi-time scales. Second, a resource-efficient communication mechanism is proposed for determining the measurement updates according to not only the measurement variations but also the realtime network conditions, realizing reasonable utilization of constrained and time-varying communication resources. Third, dual coupled monitors are developed based on state predictors and estimators for SOC/SOH co-monitoring, which provide prediction and estimation ellipsoids enclosing the true states of SOC/SOH dynamics at all times. Then, encountering potential attacks, attack detection strategies are derived by calculating the intersection over union (IOU) of the prediction and estimation ellipsoids. Upon occurrences of attacks, a compensation mechanism is presented to replace the contaminated measurement-based state estimates by the attack influence-free predicted states, suppressing the adverse effects of attacks. Finally, comparative case studies are carried out to verify the efficacy and merit of the proposed methods.